Semantic Studies: Animals in the Qur'an and Their Educational Values - Suherman, Hanan; Akmaliyah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
The Qur'an is a holy book that covers various topics, including discussions about animals. Animals, like humans, are creatures of Allah who occupy their respective positions in the Qur'an. This study is important because it reveals the deep meanings of the mention of various types of animals in the Qur'an through a semantic approach, as well as exploring the educational values ​​(qiyam tarbawiyyah) contained therein. These values ​​can be the basis for forming noble character and morals. This study aims to explore the lexical meaning, contextual meaning, and educational values ​​contained in some of the animals mentioned in the Qur'an. This study uses a semantic analysis method with a qualitative approach, which focuses on the analysis of word meaning and the study of the content of messages in the interpretation of the Qur'an. The results of the study show that several animals, such as bees, ants, spiders, frogs, lions, and dogs, have symbolic meanings that can provide valuable lessons. The characters of these animals convey educational values ​​that can be ibrah (lessons) for humans or as reminders and reprimands. The novelty of this research is that it studies animals in the Qur'an not only from the perspective of stories or biological facts, but also from the perspective of the symbolic meanings and educational values ​​they contain.